Treatment of unstable pelvic and acetabular fractures in a hospital of Bogotá D.C., Colombia: a case series - Matta-Ibarra , Javier; Arrieta-María, Víctor; Rosales-Posada, Carlos; Araya-Ramírez , Esteban; Guevara-Serna , Juan; Pérez-Oliva, Julio; Andrade-Rodríguez, Juan Carlos; Rozo-López, Gustavo (Revista Colombiana de Ortopedia y Traumatología, 2024)
Introduction: Unstable fractures of the pelvis and acetabulum (UFPA) are rare injuries caused by high-energy trauma. Their treatment is challenging due to their high morbidity and mortality. Objectives: To describe the characteristics of patients presenting with UFPA treated at the Hospital Militar Central de Bogotá D.C., Colombia, and to present flow charts for the treatment of these injuries based on the institutional experience. Methodology: Retrospective case series that included 203 patients operated on due to UFPA who were treated at the Hospital Militar Central (HMC), a quaternary care institution, between January 1992 and January 2021. The patients' sociodemographic and clinical data were obtained by reviewing their medical records. Results: The mean age of the patients was 34 years, 81.77% (n=166) were male, and the mechanism of injury was motor vehicle accident in 90.14% (n=183). It was found that 90 (44.33%) patients had fractures of the pelvic ring only, 81 (39.90%) had fractures of the acetabulum only, 25 (12.31%) had combined fractures, and 7 (3.44%) had spinopelvic dissociation. A total of 263 surgical procedures were performed: 119 (45.25%) for the treatment of pelvic ring fractures and 144 (54.75%) for the treatment of fractures of the acetabulum. Regarding fractures of the acetabulum (n=113), 2 surgical approaches were required in the same surgical procedure in some cases. Finally, adequate functional outcomes were observed in 75% of the patients at the last follow-up, and only 11.33% presented complications. Conclusion: Most of the patients with UFPA treated at the HMC during the study period were young men. There was a similar distribution of acetabular fractures and pelvic ring fractures, and the main cause of fractures was motor vehicle accidents. Furthermore, adequate functional outcomes were achieved in more than 70% of patients and the complication rate was low. Finally, the flow charts presented allow optimizing and standardizing the surgical treatment of these injuries.